Distributive mixing elements: Towards improved granule attributes from a twin screw granulation process. (24th March 2015) - Sayin, R.; El Hagrasy, A.S.; Litster, J.D.
Abstract: Granulation rate processes were studied in the distributive mixing elements (DME 1 ) of a twin screw granulator through characterization of resulting granule attributes. The screw configuration was varied by changing the orientation (forward versus reverse) and the placement of the elements (adjacent versus spaced). A model placebo formulation composed of α-lactose monohydrate, microcrystalline cellulose, hydroxypropylmethyl cellulose and croscarmellose sodium, and an aqueous granulating liquid were used in the study. Regardless of the screw configuration, DME generated granules through breakage of large wet agglomerates from the conveying section and layering of un-granulated fines. The reverse orientation produced superior granule size distribution with improved liquid distribution attributes compared to the forward orientation. The residence time distribution and flow visualization measured by a high speed imaging camera provided the mechanistic rationale for the superior behavior of the reverse over the forward DME configurations and showed the dominant granulation rate processes therein. The asymmetrical orientation of DME on the rotating shafts significantly improved the breakage capability of the reverse-placed elements, allowing a more homogeneous flow pattern of incoming granular material, with efficient layering and liquid exchange between the lumps and un-granulated fines. The results of this study demonstrate the benefit of using DME in a twin-screw wet granulation process to optimize granule attributes for downstream processing. Highlights: Twin screw wet granulation experiments using distributive mixing elements (DME). Different configurations (forward, reverse, adjacent, and spaced) of DME were used. Granule attributes, residence time and flow visualization were characterized. Reverse configurations gave mono-modal size distribution, better liquid distribution. Breakage and layering were dominant granulation rate processes in the DME section.